Cerebral β-Amyloidosis in Mice Investigated by Ultramicroscopy. - Nina Jährling; Klaus Becker; Bettina M Wegenast-Braun; Stefan A Grathwohl; Mathias Jucker; Hans-Ulrich Dodt (PLoS ONE, 2015)
Alzheimer´s disease (AD) is the most common neurodegenerative disorder. AD neuropathology is characterized by intracellular neurofibrillary tangles and extracellular β-amyloid deposits in the brain. To elucidate the complexity of AD pathogenesis a variety of transgenic mouse models have been generated. An ideal imaging system for monitoring β-amyloid plaque deposition in the brain of these animals should allow 3D-reconstructions of β-amyloid plaques via a single scan of an uncropped brain. Ultramicroscopy makes this possible by replacing mechanical slicing in standard histology by optical sectioning. It allows a time efficient analysis of the amyloid plaque distribution in the entire mouse brain with 3D cellular resolution. We herein labeled β-amyloid deposits in a transgenic mouse model of cerebral β-amyloidosis (APPPS1 transgenic mice) with two intraperitoneal injections of the amyloid-binding fluorescent dye methoxy-X04. Upon postmortem analysis the total number of β-amyloid plaques, the β-amyloid load (volume percent) and the amyloid plaque size distributions were measured in the frontal cortex of two age groups (2.5 versus 7-8.5 month old mice). Applying ultramicroscopy we found in a proof-of-principle study that the number of β-amyloid plaques increases with age. In our experiments we further observed an increase of large plaques in the older age group of mice. We demonstrate that ultramicroscopy is a fast, and accurate analysis technique for studying β-amyloid lesions in transgenic mice allowing the 3D staging of β-amyloid plaque development. This in turn is the basis to study neural network degeneration upon cerebral β-amyloidosis and to assess Aβ-targeting therapeutics.